2019
DOI: 10.1002/advs.201902230
|View full text |Cite
|
Sign up to set email alerts
|

Highly Efficient and Stable White Light‐Emitting Diodes Using Perovskite Quantum Dot Paper

Abstract: Perovskite quantum dots (PQDs) are a competitive candidate for next-generation display technologies as a result of their superior photoluminescence, narrow emission, high quantum yield, and color tunability. However, due to poor thermal resistance and instability under high energy radiation, most PQD-based white light-emitting diodes (LEDs) show only modest luminous efficiency of ≈50 lm W −1 and a short lifetime of <100 h. In this study, by incorporating cellulose nanocrystals, a new type of QD film is fabrica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
41
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 66 publications
(44 citation statements)
references
References 63 publications
0
41
0
Order By: Relevance
“…In another research for PQDs-based, Kang et al demonstrated white light emitting diodes (WLEDs) using PQD paper exhibiting an ultrahigh luminous intensity, wide color gamut, and long operational lifetime [78]. The aim of this research was to establish a cost-effective and scalable production technique to resolve high-energy radiation by demonstrating a paper manufacturing process using cellulose nanocrystals (CNCs) to manufacture a new form of PQD film.…”
Section: Perovskite Qd-based Wledmentioning
confidence: 99%
See 3 more Smart Citations
“…In another research for PQDs-based, Kang et al demonstrated white light emitting diodes (WLEDs) using PQD paper exhibiting an ultrahigh luminous intensity, wide color gamut, and long operational lifetime [78]. The aim of this research was to establish a cost-effective and scalable production technique to resolve high-energy radiation by demonstrating a paper manufacturing process using cellulose nanocrystals (CNCs) to manufacture a new form of PQD film.…”
Section: Perovskite Qd-based Wledmentioning
confidence: 99%
“…( b ) TEM image of CH 3 NH 3 PbBr 3 PQDs. ( c ) SEM of PQD paper surface [ 78 ]. Figure reproduced with permission from John Wiley and Sons.…”
Section: Figurementioning
confidence: 99%
See 2 more Smart Citations
“…PQDs are very attractive materials for QDPL-based µ-LEDs because of their excellent optical and physical properties as mentioned above. With superior colour conversion capability to generate RGB lights, PQDs have been utilised in PL-based white LEDs, and ultrahigh luminous efficiency >100 lm/W (the standard for practical use in room lighting) 122 has been achieved. For example, Zhou et al 123 developed PQDembedded polymer composite films for colour conversion, and the resulting white LEDs revealed a luminous efficiency of 109 lm/W and a wide gamut of 121% NTSC.…”
Section: Outlook Of µ-Leds and Qdsmentioning
confidence: 99%